Situational Leadership in Islamic Education: Analysis of Kiai Situational Leadership Skills at Darul Ihsan Walantaka Islamic Boarding School - Badri, Muhammad Shofwan Mawally Nafis; Gunawan, Agus; Syarifudin, Encep (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Islamic boarding schools are the oldest Islamic educational institutions in Indonesia but still exists in building and developing education in Indonesia to date. The uniqueness of the role of Islamic boarding schools is certainly inseparable from this professionalism and the intelligence of the Kiai in leading the pesantren education community. It is at this point that the main reason for this research is raised. The main focus in the discussion is the Kiai's situational leadership skills which focus on skills in diagnosing, skills flexibility his leadership style and partners for success. It is a qualitative research with a phenomenological approach. Data collection techniques with observation and interviews. Data analysis technique with data condensation, data display and conclusion drawing/verifying. The results of this study include the Kyai's skills in diagnosing by giving a potential test to the pesantren community which aims to determine the ability and commitment of subordinates. Flexibility various leadership styles depend on the competence and commitment of the pesantren community.